"Though this be Madness, yet there is Method in it": A Sociological Approach to Madness - Hughes, David J. (My University, 1972)
Sociological approach to mental illness have been dominated by the epidemiological approach. The lack of success of this approach is evidenced in the paucity of definitive findings it has produced, and in the lack of any generally accepted theory of the etiology of "schizophrenia" and the other functional mental disorders. It is the fundamental thesis of this work that the model of "schizophrenia" used by the sociologist is essentially misconstrued. Consequently, rather than suggesting methodological refinements in case finding techniques, the whole rationale underlying the epidemiological approach is subjected to a thoroughgoing critique. By treating the recurrent problems which have hampered research as investigable problems in themselves, a radially different approach to doing the sociology of mental illnesses is suggested. Rather than accepting psychiatric definitions of what constitutes a case, it is suggested that sociologists (and by implication psychiatrists) should concern themselves with the social meanings of mental illness; and treat "schizophrenia" as a label which defines the relationship between individuals and not as defining a property of an individual.
Keywords: Sociology and Anthropology; Anthropology; Sociology; Anthropology